The Guardian Angel - Holmes, Oliver Wendell, 1809-1894 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Guardian Angel" by Oliver Wendell Holmes is a novel written during the late 19th century. It explores themes of heredity, moral responsibility, and the complexities of human character through the story of Myrtle Hazard, who is depicted as a young girl navigating the tensions of her upbringing amid familial and societal expectations. At the start of the narrative, an advertisement appears in the local newspaper announcing the mysterious disappearance of Myrtle Hazard, drawing concern and speculation from the community. The opening chapters introduce various characters, including Myrtle's guardians, Miss Silence Withers and her aunt, who exemplify conflicting attitudes towards discipline and freedom. As the search for Myrtle unfolds, the chapters delve into the dynamics of the Withers family, their history, and the significant impact of heredity on Myrtle's character$1 (Ba major theme that is hinted at in the author's preface. Holmes sets a tone of intrigue and complexity, laying the foundation for a deeper exploration of Myrtle$1 (Bs struggles and the inherited traits that influence her fate. (This is an automatically generated summary.)s
Release date is 2004-09-29
Produced by David Widger
Keywords: Psychological fiction; Young women -- Fiction; Mentally ill -- Fiction; Mental illness -- Fiction; Psychotherapy patients -- Fiction